The critical role of parents within a Learning Health Network - Ferraro, Kerry; Leal, Jenny; Sutton, Anna; Peters, Susan; Pinter, Corinne (Frontiers in Pediatrics, 2024)
Parent members of the Pediatric Rheumatology Care & Outcomes Improvement Network are an integral part of the Learning Health Network’s work. Since early in the creation of the network, they have been a part of every Quality Improvement project, committee, and work group and have a role in governance on the Executive and Steering Committees. Members of the Parent Working Group (PWG) have played a role in developing QI measures used in the clinical setting as well as initiatives and projects like the guiding work of Treat-to-Target. The PWG also creates self-management supports, including toolkits for families and patients at all stages of life. This article will discuss how integrating parents as partners in a pediatric Learning Health Network is critical for the quality of care received by children with chronic illnesses and to improving outcomes.